Sosialisasi Kebijakan Lingkungan Hidup dalam Pembangunan Jalan Raya Melalui Webinar Kepada Mahasiswa Universitas Panca Bhakti - syarifah melly maulina; Sondang Sylvia Manurung; Iona Violeta (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Human activities cannot be separated from sacrificing natural resources, so that it will have an impact on the environment. Human life depends on the harmonization of the environment. Environmental and human harmony is needed by taking into account various kinds of activities, so that the quality of the environment is maintained and the survival of humans and other living creatures is guaranteed. Living things as a whole are the main cause of changes in living systems. Human activities that take into account the environment by applying science and technology appropriately. Development that is in line with the increase in population makes land less with the construction of buildings and housing. Non-renewable natural resources are increasing and human nature is frontier to the environment as one of the causes of pressure on the earth causing environmental damage. In this regard, it is necessary to know that environmental regulations in the civil sector can support appropriate environmental management patterns in current and future development. Increased knowledge of a number of issues such as climate change, increased resource consumption, population growth, and environmental degradation, must be utilized for technology development in the civil sector and formulation of regulations and policies in environmentally sustainable development strategies.